UTILIZATION OF KEPOK BANANA SKIN WASTE AS LIQUID ORGANIC FERTILIZER IN PLANTS - Sriwani Lamasrin; Adeleyda M.W. Lumingkewas (Sam Ratulangi University, 2020)
Indonesian people of all ages and social status love bananas, because the price is relatively affordable. Bananas can be consumed directly (fresh) or in processed form, for example, fried (Rohma, 2016). Kepok banana peels, if left unchecked, the banana peels can cause a buildup of garbage (Rambitan and Mirna, 2013). Based on this, a solution is needed to deal with the banana peel of Kepok. One solution that can be done is that Kepok banana peels are used and processed into organic fertilizer. The use of organic fertilizers that utilize organic waste through a decomposition process by microorganisms, can preserve the environment. Utilization of kepok banana peel waste as organic fertilizer is more useful, for example, it is processed into liquid organic fertilizer (POC). Paradoksi et al (2014) stated that liquid organic fertilizers have advantages, namely that the nutrients contained are contained more quickly and are easily absorbed by plant roots, while inorganic fertilizers have a negative impact on the environment. The results of Nabilah's research (2019) stated that Kepok banana peel fruit can be used as liquid organic fertilizer, the results of research on green spinach (Amaranthus gracilis Desf) showed an increase in plant growth, namely the length and width of the leaves at a concentration of 10 ml / L.Keywords: skin; banana; fertilizer; trashAbstrakMasyarakat Indonesia dari berbagai kalangan umur maupun status sosial menggemari pisang, karena harganya yang relatif terjangkau. Pisang dapat dikonsumsi secara langsung (segar) ataupun dalam bentuk olahan misalnya digoreng (Rohma, 2016). Kulit buah pisang kepok, apabila dibiarkan begitu saja kulit pisang tersebut dapat menyebabkan penumpukan sampah (Rambitan dan Mirna, 2013). Berdasarkan hal tersebut maka diperlukan solusi untukÂ menangani kulit buah pisang kepok. Salah satu solusi yang dapat dilakukan yaitu kulit buah pisang kepok dimanfaatkan dan diolah menjadi bahan pupuk organik. Penggunaan pupuk organik yang memanfaatkan sampah-sampah organik melalui proses dekomposisi oleh mikroorganisme, dapat menjaga kelestarian lingkungan. Pemanfaatan sampah kulit buah pisang kepok sebagai pupuk organik yang lebih bermanfaat, misalnya diolah menjadi pupuk organik cair (POC). Paradoksi dkk (2014) menyatakan bahwa pupuk organik cair memiliki kelebihan yakni unsur hara yang dikandung lebih cepat dan mudah diserap oleh akar tanaman, sedangkan pupuk anorganik memiliki dampak negatif terhadap lingkungan. Hasil penelitian Nabilah (2019) menyatakan bahwa buah kulit pisang kepok dapat dijadikan pupuk organik cair, hasil penelitian pada tanaman bayam hijau (Amaranthus gracilis Desf) menunjukkan peningkatan pertumbuhan tanaman yaitu panjang dan lebar daun pada pemberian konsentrasi 10 ml/L.Kata kunci: kulit; pisang; pupuk; sampah